Schistosoma mekongi: The in vitro effect of praziquantel and artesunate on the adult fluke - Wannee Jiraungkoorskul (2018)
The efficacy and tolerance of 80 μg/ml praziquantel (PZQ) and 40 μg/ml artesunate (ATS) against adult stage Schistosoma mekongi in vitro were investigated after 3, 6, 12, and 24 h incubation by monitoring worm motility and compared tegumental changes using scanning electron microscopy (SEM). Thirty mice were infected with S. mekongi cercaria for 49 days. Adult worms were collected by perfusion method and prepared for in vitro study. Contraction and decreased motor activity were observed after as little as 3 h incubation with PZQ and ATS. Some of the worms were immobile 12 h after exposure, and died within 24 h. The tegument of S. mekongi showed severe swelling, vacuolization and disruption, fusion of the tegumental ridges, collapse and peeling. After 12-24 h incubation, PZQ induced similar but they less severe, tegumental changes to those observed after exposure to ATS. The direct observation of the fluke motility and SEM study suggest that ATS is more effective than PZQ in causing tegumental damage in adult S. mekongi, and provides a basis for subsequent clinical trials. © 2005 Elsevier Inc. All rights reserved.